Horseback riding-related injuries treated in emergency departments: Risk factors and prevention strategies. (December 2019) - Asa, Nicole; Newton, Alison; Sullivan, Lindsay; Shi, Junxin; Wheeler, Krista; Smith, Gary A.; Yang, Jingzhen
Abstract: Introduction: Despite inherit dangers of horseback riding (HBR), research on HBR-related injuries is sparse. This study used both quantitative and qualitative methods to (1) examine HBR-related injuries treated in emergency departments (EDs) and associated risk factors and (2) explore HBR-related injury experiences and recommendations for prevention strategies from the perspective of riders. Method: We retrospectively analyzed data from the Nationwide Emergency Department Sample (NEDS), identifying HBR-related ED visits between 2010 and 2014. Additionally, we conducted 10 phone interviews with active horseback riders to understand their experiences and perspectives regarding HBR-related injuries and recommendations for prevention measures. Results : A total of 21, 899 ED visits for HBR-related injuries were identified. When weighted, these represented 100, 964 ED visits in the United States. Females had a consistently higher proportion of ED visits compared to males across the study period, with the proportion of ED visits being highest in females aged 15–19. Most injuries (85.9%) were treated and released from the ED. Three primary themes were identified as key to the prevention of HBR-related injuries: (1) rider safety (e.g., use of protective equipment), (2) external factors (e.g., awareness of environment), and (3) rider and horse interactions (e.g., matching skill level of the rider to the horse). Conclusions: Results indicate that HBR-related injuries treated in EDs are prevalent, with female riders aged 15–19 years having the highest proportion of injuries treated in EDs. Practical Applications: There is a critical need for injury prevention programs that not only promote the use of protective equipment, but that also educate horseback riders on horse behavior, the proper handling of horses, and safe riding practices.